Controller design for VSCs in distributed generation applications: An IDA-PBC approach (2019)
This paper presents an asymptotically stable global controller design for distributed energy integration in electrical distribution networks using a three-phase voltage source converter (VSC). An invariant Park's transformation is used to obtain the mathematical representation of the VSC in dq0 reference frame. To design of the proposed controller, interconection and damping assignment passivity-based control (IDA-PBC) theory is applied via a Hamiltonian representation for the open-loop dynamic as well as the desired closed-loop dynamic of the system. The control law obtained allows guaranteeing asymptotic stability properties in the sense of Lyapunov for closed-loop operation. To verify the robustness and effectiveness of the proposed controller a classic connection of a distributed generator with a VSC converter using an ideal voltage source in its DC side is employed. Simulation results show the capability of the proposed controller to support active and reactive power independently under unbalance voltage conditions and harmonic distortion as well as the possibility of using the VSC as a dynamic power factor corrector. Additionally, all simulation scenarios are compared to classic PI controllers to show the good dynamic performance of the proposed controller using IDA-PBC theory. MATLAB/SIMULINK software is employed as simulation environment. © 2018 IEEE.